The Pactum De Non Cedendo: through a constitutional lens - Abrahams, Ebrahim (Department of Private Law, 2017)
The aim of this paper was to determine whether the current South African law governing the doctrine of pacta de non cedendo complies with the constitutional mandates imposed by our Constitution. In terms of the current law a pactum de non cedendo will only be accorded validity if the debtor is able to demonstrate a substantial interest in the prohibition against cession. However, the interest requirement is only applicable when a pactum de non cedendo is superimposed onto a pre-existing right, and is not required when a right is born ab initio with a prohibition on transfer. In my opinion the current law falls short of the "spirit, purport and objects of the Bill of Rights", as required by s 39(2) of the Constitution, and is therefore, in need of development. In this paper I propose the following development: Firstly, by requiring the debtor to prove an interest that is served by the pactum de non cedendo, in certain circumstances, the law undermines the value of equality held so dearly by our society. This is because no such requirement exists when other types of restrictive clauses are concluded. It is my contention that the "interest requirement" be relegated from being a free-standing requirement to simply being another factor to be taken into account when conducting the public policy enquiry. Secondly, pacta de non cedendo appearing in book debts and other similar monetary obligations should always be held contrary to public policy due to the importance of the free flow of claims in commerce, specifically, the factoring and securitisation industries. Factoring plays a crucial role in the world economy, the most advantageous aspect of factoring is that small to medium size businesses may obtain much needed finance by selling their claims to a factoring house. Lastly, the current distinction drawn between a pactum de non cedendo that is superimposed onto a pre-existing right, and a right that is created with a pactum de non cedendo is artificial and illogical, the correct distinction that should be drawn is between a pactum de non cedendo that is concluded by the debtor and creditor on the one hand, and between a pactum de non cedendo concluded between the cedent and cessionary on the other.